Statistical analysis of factors affecting monoclonal antibody production by using principal component analysis : physiological characteristics of cell line - Wong, Shin Yie (2018)
Rapid increase in the demand for biopharmaceutical products has posed a challenge in the selection of high producing cell line that produce maximum amount of product. Various advances and efforts has been done on cell culture technology for Chinese Hamster Ovary (CHO) cell lines to achieve an improvement in the specific productivity of CHO cell lines. This study identifies the effects and relationship of various physiological characteristics of a panel of six CHO stable cell lines on the specific productivity (qp) of cell lines ranging from 2 to 50 pg/cell/day. We examined the correlation between physiological characteristics and specific productivity throughout the growth phase of batch culture. Results obtained were statistically analysed using Principal Component Analysis (PCA). Our research revealed that, overall, specific productivity is positively correlated to the total intracellular protein content of the cell lines. Meanwhile, specific productivity is negatively correlated to the cell density throughout the development of cell lines. However, this correlation was not observed at all-time points throughout the growth phase. Another significant finding from the research is that the correlation between physiological characteristics and specific productivity was the strongest during late exponential 5 of the growth phase as compared to early exponential.